2007
DOI: 10.1128/cmr.00010-06
|View full text |Cite
|
Sign up to set email alerts
|

Viral Determinants of Resistance to Treatment in Patients with Hepatitis C

Abstract: SUMMARY Chronic hepatitis C virus (HCV) infection affects more than 170 million persons worldwide and is responsible for the development of liver cirrhosis in many cases. Standard treatment with pegylated alpha interferon (IFN-α) in combination with the nucleoside analogue ribavirin leads to a sustained virologic response in approximately half of the patients. IFN-α is classified as an indirect treatment, as it interacts with the host's immune response. The mechanism of action of ribavirin is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
118
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 167 publications
2
118
1
3
Order By: Relevance
“…This treatment is effective in Ϸ50% of patients (1, 3). Resistance to IFN and ribavirin (4), and HCV persistence after SVR in the form of ''occult'' hepatitis C (3,5) makes HCV frequently incurable. The virus effectively avoids the host immune response and no vaccine for hepatitis C is currently available (6,7).…”
mentioning
confidence: 99%
“…This treatment is effective in Ϸ50% of patients (1, 3). Resistance to IFN and ribavirin (4), and HCV persistence after SVR in the form of ''occult'' hepatitis C (3,5) makes HCV frequently incurable. The virus effectively avoids the host immune response and no vaccine for hepatitis C is currently available (6,7).…”
mentioning
confidence: 99%
“…The PCR products were purified and sequenced individually on both strands ( RNA concentration of HCV, age, gender, body mass index (BMI), fibrosis stage, alanine aminotransferase (ALT), gamma-glutamyl-transpeptidase (GGT) levels, insulin resistance, and host genetic polymorphism of several genes (human leukocyte antigen, chemokines, ILs, and IFNstimulated genes) are associated with SVR. 16,17 Presently, in clinical practice guidelines, only the HCV genotype and concentration of HCV-RNA at baseline are recommended to be used in determining treatment duration but still the therapy is frequently complicated by treatment-limiting side effects. [18][19][20][21] The most recent genome-wide association studies reported association of different SNPs of IL28B gene (IFN-λ gene region) with response to antiviral therapy, where SNP, rs12979860(C/T) of IL28B gene, was reported to be strongly associated.…”
Section: Genotyping Of Il28b Polymorphism (Rs12979860c/t)mentioning
confidence: 99%
“…Despite a significant research effort, only half of patients infected with HCV genotype 1 respond to therapy (50). IFN clearly plays an important role in HCV treatment response.…”
mentioning
confidence: 99%